1969
DOI: 10.15281/jplantres1887.82.271
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the Hill Reaction in Spinach Chloroplasts by Pre-treatment of Tris Buffer in the Light

Abstract: By pre-treatment of spinach chloroplasts with a high concentration of Tris buffer, 0.8 M, pH 8. 0, oxygen evolution coupled with DPIP or ferricyanide photoreduction was inactivated only when the chloroplasts were incubated in the light , but not in the dark. This inactivation of the chloroplast reaction was not due to chemical decomposition of Tris, but was probably due to the photoinhibition as reported by others. The photoinhibition was protected by the addition of DPIP in either oxidized or reduced form.It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1971
1971
1991
1991

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Irreversible inhibition of 0, evolution upon incubation of PSII in 0.8 M Tris in the dark was reported earlier by Ikehara and Sugahara (1969) and Cheniae and Martin (1978), but the mechanism was not studied in detail. More work has been focused on the light-induced inactivation of 0, evolution by Tris (Yamashita & Horio, 1968).…”
Section: Discussionmentioning
confidence: 87%
“…Irreversible inhibition of 0, evolution upon incubation of PSII in 0.8 M Tris in the dark was reported earlier by Ikehara and Sugahara (1969) and Cheniae and Martin (1978), but the mechanism was not studied in detail. More work has been focused on the light-induced inactivation of 0, evolution by Tris (Yamashita & Horio, 1968).…”
Section: Discussionmentioning
confidence: 87%
“…Aged Tris-buffer yielded formaldehyde and inhibited chloroplasts [2]. Tris has a primary amino group which become non-ionic form (R-NH2) at higher pHs and inhibit chloroplasts [7][8]II]. Inactivation of chloroplasts by Tris-washing was stimulated by illumination (i000 lux), especially at pH lower than 8.0 [7].…”
Section: The Site and The Mechanism Of Tris-inactivationmentioning
confidence: 99%
“…Tris has a primary amino group which become non-ionic form (R-NH2) at higher pHs and inhibit chloroplasts [7][8]II]. Inactivation of chloroplasts by Tris-washing was stimulated by illumination (i000 lux), especially at pH lower than 8.0 [7]. Single and double flashes were more effective than triple flashes in stimulating the inactivation.…”
Section: The Site and The Mechanism Of Tris-inactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to affect many biological processes including ion transport (Van Steveninck 1961, 1966a, 1966bKholdebarin and Oertli 1970), the Hill reaction (Jacobi 1961), uncoupling of photosynthetic phosphorylation (Good 1962), isolation of mitochondria (Stinson and Spencer 1968), sucrose storage (Humphreys and Garrard 1969), and amino acid incorporation (Bewley and Marcus 1970). Ikehara and Sugahara (1969) suggested that Tris at high pH may alter the structure of chloroplast lamellae. A possible effect of Tris on membrane structure was suggested also by Humphreys and Garrard (1969) and by Yamashita, Tsuji, and Tomita (1971).…”
Section: Introductionmentioning
confidence: 99%